A Rapid, Direct, Quantitative, and Label‐Free Detector of Cardiac Biomarker Troponin T Using Near‐Infrared Fluorescent Single‐Walled Carbon Nanotube Sensors. Issue 3 (21st August 2013) - Zhang, Jingqing; Kruss, Sebastian; Hilmer, Andrew J.; Shimizu, Steven; Schmois, Zeke; De La Cruz, Flor; Barone, Paul W.; Reuel, Nigel F.; Heller, Daniel A.; Strano, Michael S.
<x xml:space="preserve">Abstract</x> Patients with chest pain account for 10% of US emergency room visits according to data from the Center for Disease Control and Prevention (2013). For triage of these patients, cardiac biomarkers troponin I and T are endorsed as standard indicators for acute myocardial infarction (AMI, or heart attack). Thus, there is significant interest in developing a rapid, point‐of‐care (POC) device for troponin detection. In this work, a rapid, quantitative, and label‐free assay, which is specific for cardiac troponin T (cTnT) detection, using fluorescent single‐walled carbon nanotubes (SWCNTs), is demonstrated. Chitosan‐wrapped carbon nanotubes are cross‐linked to form a thin gel that is further functionalized with nitrilotriacetic acid (NTA) moieties. Upon chelation of Ni2+, the Ni2+‐NTA group binds to a hexa‐histidine‐modified troponin antibody, which specifically recognizes the target protein, troponin T. As the troponin T binds to the antibody, the local environment of the sensor changes, allowing direct troponin detection through intensity changes in SWCNT bandgap fluorescence. This platform represents the first near‐infrared SWCNT sensor array for cTnT detection. Detection can be completed within 5 min, demonstrating a linear response to cTnT concentration and an experimental detection limit of 100 ng mL−1 (2.5 nm). This platform provides a promising new tool for POC AMI detection in the future. Moreover, the work presents two new methods of quantifying the number of amines and carboxylic groups, respectively, in a carbon hydrogel matrices.